Schaum's Signals and Systems Problem 2.30 : Using MATLAB to find the discrete-time convolution - Berry, Carlotta (McGraw-Hill's AccessEngineering., 2020)
This video will show how to use convolution in MATLAB to find the output for a discrete-time LTI system given the input and impulse response.